Role of Estrogen Receptors α and β in a Murine Model of Asthma: Exacerbated Airway Hyperresponsiveness and Remodeling in ERβ Knockout Mice - Kalidhindi, Rama Satyanarayana Raju; Ambhore, Nilesh Sudhakar; Bhallamudi, Sangeeta; Loganathan, Jagadish; Sathish, Venkatachalem (Frontiers in Pharmacology, 2020)
Epidemiological data suggests increased prevalence of asthma in females than males, suggesting a plausible role for sex-steroids, especially estrogen in the lungs. Estrogen primarily acts through estrogen-receptors (ERα and ERβ), which play a differential role in asthma. Our previous studies demonstrated increased expression of ERβ in asthmatic human airway smooth muscle (ASM) cells and its activation diminished ASM proliferation in vitro and airway hyperresponsiveness (AHR) in vivo in a mouse (wild-type, WT) model of asthma. In this study, we evaluated the receptor specific effect of circulating endogenous estrogen in regulating AHR and remodeling using ERα and ERβ knockout (KO) mice. C57BL/6J WT, ERα KO and ERβ KO mice were challenged intranasally with a mixed-allergen (MA) or PBS. Lung function was measured using flexiVent followed by collection of broncho-alveolar lavage fluid for differential leukocyte count (DLC), histology using hematoxylin and eosin (H&E) and Sirius red-fast green (SRFG) and detecting α-smooth muscle actin (α-SMA), fibronectin and vimentin expression using immunofluorescence (IF). Resistance (Rrs), elastance (Ers), tissue-damping (G) and tissue-elasticity (H) were significantly increased, whereas compliance (Crs) was significantly decreased in WT, ERα KO and ERβ KO mice (males and females) challenged with MA compared to PBS. Interestingly, ERβ KO mice showed declined lung function compared to ERα KO and WT mice at baseline. MA induced AHR, remodeling and immune-cell infiltration was more prominent in females compared to males across all populations, while ERβ KO females showed maximum AHR and DLC, except for neutrophil count. Histology using H&E suggests increased smooth muscle mass in airways with recruitment of inflammatory cells, while SRFG staining showed increased collagen deposition in MA challenged ERβ KO mice compared to ERα KO and WT mice (males and females), with pronounced effects in ERβ KO females. Furthermore, IF studies showed increased expression of α-SMA, fibronectin and vimentin in MA challenged populations compared to PBS, with prominent changes in ERβ KO females. This novel study indicates ERβ plays a pivotal role in airway remodeling and AHR and understanding the mechanisms involved might help to surface it out as a potential target to treat asthma.